Changing wildlife populations in Nairobi national park and adjoining Athi-Kaputiei plains: Collapse of the migratory Wildebeest - Ogutu, Joseph O.; Owen-Smith, N.; Piepho, Hans-Peter; Said, Mohammed Yahya; Kifugo, S.C.; Reid, Robin S.; Gichohi, H.; Kahumbu, P.; Andanje, S. (Bentham Science Publishers Ltd., 2013)
There is mounting concern about declines in wildlife populations in many protected areas in Africa. Migratory ungulates are especially vulnerable to impacts of changing land use outside protected areas on their abundance. Range compression may compromise the capacity of migrants to cope with climatic variation, and accentuate both competitive interactions and predation. We analyzed the population dynamics of 11 ungulate species within Kenya’s Nairobi National Park, and compared them to those in the adjoining Athi-Kaputiei Plains, where human settlements and other developments had expanded. The migratory wildebeest decreased from almost 30,000 animals in 1978 to around 5,000 currently but the migratory zebra changed little regionally. Hartebeest, impala, eland, Thomson’s gazelle, Grant’s gazelle, waterbuck, warthog and giraffe numbers declined regionally, whereas buffalo numbers expanded. Bimonthly counts indicated temporary movements of several species beyond the unfenced park boundaries, especially during very wet years and that few wildebeest entered the park during the dry season following exceptionally wet conditions in 1998. Wildebeest were especially vulnerable to anthropogenic impacts in their wet season dispersal range on the plains. Deterioration in grassland conditions in the park following high rainfall plus lack of burning may have discouraged these animals from using the park as a dry season refuge. Our findings emphasise the interdependency between the park and the plains for seasonal wildlife movements, especially in exceptionally dry or wet years. To effectively conserve these ungulates, we recommend implementation of the new land-use plan for the Athi-Kaputiei Plains by the county government; expansion of the land leasing program for biodiversity payments; collecting poacher’s snares; negotiation and enforcement of easements, allowing both wildlife and livestock to move through the Athi-Kaputiei Plains, providing incentives for conservation to landowners; and improving grassland conditions within the park through controlled burning so that more wildlife can gain protection there.